HISTORICAL, NATIONAL CULTURAL FEATURES OF TOPONYMS IN TURAN AND GREAT BRITAIN - B.J.KARAYEVA; E.АLKAYA; A.K.MEIRBEKOV (Research Retrieval and Academic Letters, 2025)
. It can be said that toponymy occupies a huge place in the life of society. After all, people's life, historical and social actions take place in all frames of the geographical environment, in specific territorial complexes consisting of many objects with their own names. Therefore, the names of Kazakh-English place names at all times perform a wide variety of tasks, without which the existence of a social formation would be difficult. The growing flow of international exchange of diverse information in the ethnolinguistic, historical direction has made geographical names very necessary and obligatory attributes of our daily life. This article investigates the study of the ethnocultural and historical features of the toponyms of the Great Turan region of the Kazakh and Britain region, taking into account the peculiarities of the Kazakh and English toponyms. The results of the study show that the main features of the toponymic image of the Kazakh and English people are associated with historical meanings, the availability of information about the physical characteristics of the region, the manifestation of cultural heritage, the influence of linguistic processes, social, cultural and historical factors, the presence of emotional coloring, stories or even tragic events. In this context, the study of toponymic national cultural values of any onomastics language is a great importance both field of the science and for linguistics. Toponyms constantly replenished and updated, served and serve the comprehensive needs of both the past and modern society.They serve future generations, being a continuing tool of history.In the course of the study were used methods of description, classification, generalization, comparative-historical.The study of Kazakh and English toponymic names do not only enriches theoretical knowledge in this field, but also contributes to the deepening of knowledge about cultural exchange and development, national values of the two countries, as well as a comprehensive understanding of top